Developmental Nexus between Socio-Economic and Cultural Correlates of Exclusive Breastfeeding among Nursing Mothers in Ojo Local Government Area of Lagos State, Nigeria - Oduwole, Tajudeen Adebowale (Advances in Social Sciences Research Journal, 2016)
Development as a social discourse, a construct that has been arguably conceptualized as a journey and not a destination, equally a many-sided process by pool of scholars and writers of both the antediluvian and in our contemporary time. The discourse touch light its curiosity on the nexus between socio-economic and cultural correlates of exclusive breastfeeding among nursing mothers in Ojo Local Government Area of Lagos State, Nigeria. Other specific interests of the paper are the pattern of exclusive breastfeeding, the level of literacy of nursing mothers and the socio-economic state of the nation, its effects, if any, on the lactating mothers in the study area. A survey of one hundred and fifty mothers were selected, using simple random sampling, questionnaires were administered. Chi-square statistical analysis was carried out to evaluate relationship among selected variables for the study. The study revealed 17.9% of mothers’ breastfed their children exclusively for the first 6 months, and the mean duration of exclusive breastfeeding (EBF) is 2.1 months. Complementary feeding was more commonly initiated around 4 – 6months (75.2%). The fact that 60.6% of mothers initiate breastfeeding and 21.6% of mothers are found to breastfeed up to 2 years, the practice of EBF for the first 6 months is low (17.9%). Causal factors militating EBF, are type of delivery, occupation of the mothers, education, and thorough awareness. Therefore, the strongest thrust of this paper is that proper initiation programmes by the relevant agencies of health practitioners should endeavour more orientation about the benefit of exclusive breastfeeding to the community (Ojo).